Tradition as a basis for the formation of political culture of china - Kaskarauova, А. (Journal of Oriental Studies, 2016)
This article examines the ideological line of the current leadership, which is caused by a combination of modern culture and thefinest achievements of traditional Chinese culture. Analyze the influence of the ancient traditions of China’s current model of China’smodernization.